94 The T cell antigen coupler (TAC) redirects T cell oncolysis while limiting tonic signaling to create a safer engineered T cell product with a higher threshold for activation. (10th December 2020) - Moogk, Duane; Lau, Vivian; Afsahi, Arya; Dvorkin-Gheva, Anna; Bezverbnaya, Ksenia; Hammill, Joanne; Bramson, Jonathan
Abstract : Background: The T cell Antigen Couper (TAC) is a chimeric receptor that redirects the endogenous T cell receptor (TCR) against a tumor target via an extracellular antigen-binding domain to induce activation and oncolysis. TAC-engineered T cells (TAC-T cells) showed a similar capacity to activate T cells against the tumor-associated antigen HER2 as their classical chimeric antigen receptor (CAR)-engineered counterparts in vitro. However, in a xenograft model, anti-HER2 CAR-T cells gave rise to lethal off-target toxicity while TAC-T cells were efficacious and well-tolerated, despite utilizing the same antigen-binding domain. 1 2 Here, we describe differences in T cell activation by TAC (canonical via endogenous TCR) and CAR (non-canonical independent of TCR) that make CAR-T cells less discriminate towards an off-target stimulus than TAC-T cells. Methods: Paired sets of TAC- and CAR-engineered human T cells, utilizing a variety of antigen-binding domains, were compared in vitro to determine their propensity for tonic signaling and requirements for triggering T cell activation. Results: Transcriptional profiling of CAR- and TAC- T cells in the absence of antigenic stimulus revealed an elevated basal activation status in CAR-T cells. Unstimulated CAR-T cells displayed elevated expression levels of activation and exhaustion markers, as well as basal cytokine production, versus their TAC-T cell counterparts. The degree of basal activation varied with the binding domain incorporated into the CAR, where some binding domains triggered functional exhaustion. Regardless of the binding domain, unstimulated TAC-T cells were indistinguishable from control T cells that expressed no synthetic receptor. Further, TAC-T cells displayed no evidence of functional exhaustion. TCR knock-out studies confirmed that TAC receptors signal via the endogenous TCR, whereas CAR signaling is TCR-independent. Consistent with TCR-dependent signaling, ligation of TAC receptors resulted in the formation of conventional immunological synapses, whereas ligation of CARs produced unconventional synapses. Despite these functional differences, CARs and TAC receptors demonstrated a similar capacity to activate T cells against antigen-positive tumor cell targets. However, CAR-T cells displayed reactivity to antigen-negative cells, due to interaction with a cross-reactive antigen; TAC-T cells displayed no reactivity to antigen-negative cells. Conclusions: Tonic signaling in CAR-T cells reduces their activation threshold and increases their propensity to be activated by cross-reactive antigen. In contrast, TAC receptors do not deliver tonic signals, which increases the stringency of activation and reduces the likelihood of off-target responses. This feature of the TAC platform is advantageous to safeguard against the unexpected cross-reactivity that may occur when a new antigen-binding domain is deployed in vivo. Ethics Approval: Use of human materials was approved by the Hamilton Integrated Research Ethics Board (HiREB). References: Helsen C, Hammill JA, Lau VWC, Mwawasi KA, Afsahi A, Bezverbnaya K, Newhook L, Hayes DL, Aarts C, Bojovic B, Denisova GF, Kwiecien JM, Brain I, Derocher H, Milne K, Nelson BH, Bramson JL. The chimeric TAC receptor co-opts the T cell receptor yielding robust anti-tumor activity without toxicity. Nat Commun 2018;9 :3049. Hammill JA, Kwiecien JM, Dvorkin-Gheva A, Lau VWC, Baker C, Wu Y, Bezverbnaya K, Aarts C, Helsen CW, Denisova GF, Derocher H, Milne K, Nelson BH, Bramson JL. A cross-reactive small protein binding domain provides a model to study off-tumor CAR-T cell toxicity. Mol Ther Oncolytics 2020;17 :278–292.